Mixed R&D incentives: the effect of R&D subsidies on patented inventions - Cedric Schneider (Copenhagen Business School (CBS), Department of Economics, 2008)
This paper analyzes the effects of mixed public-private R&D incentives and empirically tests whether patents that were publicly sponsored are more important than non-subsidized ones. Blending patents and public subsidies will allow the funding agency to subsidize inventions that would otherwise not elicit investment because the private incentive will not fully cover the cost of the invention. Thus, the policy maker will only subsidize inventions that have a high social value. The empirical analysis shows that subsidized inventions result in more important patents, as measured by the number of forward citations.
hdl:10398/7662
Keywords: G10; 330